Calcification of arteries supplying the gastric tube increases the risk of anastomotic leakage after esophagectomy with cervical anastomosis - Zhao, Liang (J Thorac Dis, 2016)
BACKGROUND: Anastomotic leak is an important cause of morbidity and mortality after esophagectomy for esophageal cancer patients. Calcification of the arteries supplying the gastric tube has been found to be associated with leakage after esophagectomy with cervical anastomosis in Europeans. The purpose of this study is to evaluate the association between calcifications of the supplying arteries of the gastric tube and the occurrence of anastomotic leakage after esophagectomy with cervical anastomosis in Chinese patients with esophageal cancer. METHODS: The demographic, clinical, and pathological features as well as the vascular calcification of arteries of 709 esophageal cancer patients who had undergone esophagectomies with cervical anastomosis were analyzed. Univariable and multivariable logistic regression were used to identify the association between the postoperative anastomotic leakage and calcifications of the arteries supplying the gastric tube. RESULTS: Among the 709 patients, 122 (17.2%) had developed anastomotic leakage. Thirty-day mortality and length of hospital stay were higher for patients with anastomotic leakage. Upper digestive tract ulcer, peripheral vascular disease, renal insufficiency, American society of Anesthesiologists (ASA) risk class, and calcifications of aorta and celiac axis were found to be independent risk factors for the anastomotic leakage. CONCLUSIONS: Calcification of the aorta and celiac axis that supply the gastric tube is an independent risk factor for cervical anastomotic leakage after esophagectomy in Chinese esophageal cancer patients.